2020
DOI: 10.1111/ctr.14133
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐ and macrovascular cardiac allograft vasculopathy in relation to 91 cardiovascular biomarkers in heart transplant recipients—An exploratory study

Abstract: Background Cardiac allograft vasculopathy (CAV) limits survival after heart transplantation (HTx), and the pathogenesis is not fully clarified. We aimed to investigate a wide range of biomarkers and their correlation with micro‐ and macrovascular CAV and major adverse cardiac events in HTx patients. Methods We evaluated 91 cardiovascular disease‐related proteins in 48 HTx patients using a novel proteomic panel. Patients were dichotomized according to micro‐ and macrovascular CAV burden determined by coronary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…A study in 2020 by Bjerre et al further evaluated 91 cardiovascular disease related proteins, identifying two novel, potentially significant recipient biomarkers [ 113 ]. Specifically, HTx patients with diagnosed CAV had significantly deranged serum levels of subtilisin/kexin type 9 (PCSK9) and paraoxonase 3 (PON3), both of which are involved in cholesterol homeostasis [ 113 ]. This adds evidence to the hypothesis that, despite its differences with native heart atherosclerosis, cholesterol accumulation is significant in the pathogenesis of CAV.…”
Section: Biomarkersmentioning
confidence: 99%
“…A study in 2020 by Bjerre et al further evaluated 91 cardiovascular disease related proteins, identifying two novel, potentially significant recipient biomarkers [ 113 ]. Specifically, HTx patients with diagnosed CAV had significantly deranged serum levels of subtilisin/kexin type 9 (PCSK9) and paraoxonase 3 (PON3), both of which are involved in cholesterol homeostasis [ 113 ]. This adds evidence to the hypothesis that, despite its differences with native heart atherosclerosis, cholesterol accumulation is significant in the pathogenesis of CAV.…”
Section: Biomarkersmentioning
confidence: 99%
“…Consistent changes in 2 proteins PON3 and PCSK9 were observed. 58 These proteins are involved in cholesterol homeostasis and thus may be important players in CAV pathogenesis. N-terminal pro-brain natriuretic peptide was found to be elevated in patients with microvascular CAV.…”
Section: Heart Transplantmentioning
confidence: 99%
“…Other biomarkers, such as Troponin and CRP have been studied mainly in the adult population with mixed results. BNP, a hormone secreted by the ventricles in response to myocardial stress, has been shown in adult studies to be associated with the presence of CAV and allograft dysfunction 47,48 . A few studies looking at BNP as a biomarker were done in the pediatric population in the early 2000s demonstrating a role for BNP in the detection of acute rejection and graft loss with evidence of overlap with CAV 10 .…”
Section: Diagnosis Of Cavmentioning
confidence: 99%
“…BNP, a hormone secreted by the ventricles in response to myocardial stress, has been shown in adult studies to be associated with the presence of CAV and allograft dysfunction. 47,48 A few studies looking at BNP as a biomarker were done in the pediatric population in the early 2000s demonstrating a role for BNP in the detection of acute rejection and graft loss with evidence of overlap with CAV. 10 A study looking at 37 patients post pediatric heart transplant demonstrated a significant difference in BNP levels in patients with graft pathology compared to those without (p < .001).…”
Section: Biomarkersmentioning
confidence: 99%